Peran Pemerintah Daerah Dalam Pencegahan Perkawinan Anak - Indra Kertati (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Child marriage occurred long before the emergence of the Marriage Law number 1 of 1974 and its amendment, namely Law number 16 of 2019. The difference lies in the reason for the marriage itself. Long before the reason for underage marriages was a growing culture that women were considered sufficient to be at home, and to be the mother of the children they were born with. The strengthening patriarchal culture has an impact on the marginalization of women. The term women are kitchens, mattresses, legendary wells and perpetuate underage marriages. Issues that develop are different because child marriage now leads to promiscuity. The problem currently encountered is the increasing number of child marriages. The purpose of this study was to analyze the role of local government in preventing child marriage, with the locus in Grobogan Regency. This research used a qualitative descriptive approach. The results of the study show that the role of local government is not optimal. Prevention of child marriage is not as easy as solving other social problems. Family isolation, and scattered locations make it difficult for local governments to control child marriage. The role of stakeholders in preventing child marriage is not strong. Child marriage is considered a sensitive area that is not easy to touch.